2021
DOI: 10.48022/mbl.2106.06013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heavy Metal Tolerant and Plant Growth-Promoting Rhizobacteria Isolated from Soil Contaminated with Heavy Metal and Diesel

Abstract: In order to enhance rhizoremediation performance, which remediates contaminated soils using the interactions between plants and microorganisms in rhizosphere, it is required to develop effective microbial resources that simultaneously degrade contaminants and promote plant growth. In this study, heavy metal-resistant rhizobacteria, which had been cultivated in soils contaminated with heavy metals (copper, cadmium, and lead) and diesel were isolated from rhizospheres of maize and tall fescue. After that, the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Like the current observation, soil isolates recovered from metal polluted soil have been reported to displayed a dissimilar heavy metal tolerance profile 24 . Similarly, PGPR strain like Bacillus sp., Cupriavidus sp., Cupriavidus sp., Fulvimonas soli and Novosphingobium sp., isolated from rhizosphere soil tolerated heavy metal concentrations 43 . In yet another study, Fahsi and co-workers 44 reported that Enterobacter hormaechei J-146 could withstand up to 1.5 mg L −1 of Cu/Cd, while B. halotolerans J-143 could tolerated up to 1.5 mg L −1 of Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Like the current observation, soil isolates recovered from metal polluted soil have been reported to displayed a dissimilar heavy metal tolerance profile 24 . Similarly, PGPR strain like Bacillus sp., Cupriavidus sp., Cupriavidus sp., Fulvimonas soli and Novosphingobium sp., isolated from rhizosphere soil tolerated heavy metal concentrations 43 . In yet another study, Fahsi and co-workers 44 reported that Enterobacter hormaechei J-146 could withstand up to 1.5 mg L −1 of Cu/Cd, while B. halotolerans J-143 could tolerated up to 1.5 mg L −1 of Ni.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the PGP properties of strain CuT1, indole-3-acetic acid (IAA), siderophore, and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase production were investigated as described by Lee et al (2021a).…”
Section: Isolation and Identi Cation Of A Heavy Metal Tolerance And P...mentioning
confidence: 99%
“…The diesel concentration extracted from the supernatant was measured via a gas chromatography (GC 6980N system, Agilent Technologies, CA, USA) equipped with a ame ionization detector (FID; Agilent Technologies) and an HP-5 capillary column (30 m × 0.320 mm × 0.25 µm, Agilent Technologies). All procedures were performed as described in our previous report (Lee et al, 2021a). The diesel removal e ciency was calculated as a percentage by comparing the initial diesel concentration with the residual diesel concentration after two weeks.…”
Section: Characterization Of the Heavy Metal Tolerance And Diesel Deg...mentioning
confidence: 99%
“…The structures of these compounds were elucidated by the examination of their ESI-MS and NMR ( 1 H NMR, 13 C NMR, HMBC, HSQC) spectra (Figures S1-S20) and comparison with reported data. The compounds were identified as cyclo(L-Pro-L-Tyr) (1) (Wattana-Amorn et al, 2016), macrolactin A (2) (Lee et al, 2004;Romero-Tabarez et al, 2006), macrolactin H (3) (Nagao et al, 2001), and 15,17-epoxy-16-hydroxy macrolactin A (4) (Mondol et al, 2011).…”
Section: Isolation and Identification Of The Compounds Produced By Ba...mentioning
confidence: 99%
“…Although numerous macrolide compounds have been isolated and identified from sponges and their symbionts (Karpiński, 2019), this is the first study to report the isolation of macrolactins from sponge-associated bacteria. Macrolactin A (2) has been frequently isolated from different bacteria (Nagao et al, 2001;Lee et al, 2004;Romero-Tabarez et al, 2006;Lu et al, 2008;Kim et al, 2011;Tareq et al, 2013;Li et al, 2016a), whereas macrolactin H (3) and 15, 17-epoxy-16-hydroxy macrolactin A (4) have been rarely isolated (Nagao et al, 2001;Mondol et al, 2011). Previous bioassays revealed that macrolactin A exhibited antimicrobial activity against Gram-negative bacteria (i.e., E. coli), Gram-positive bacteria (i.e., S. (Nagao et al, 2001;Lee et al, 2004;Romero-Tabarez et al, 2006;Lu et al, 2008;Kim et al, 2011;Tareq et al, 2013;Li et al, 2016a).…”
Section: Antimicrobial Activity Of Sponge-associated Bacteriamentioning
confidence: 99%